2013
DOI: 10.1289/ehp.1206178
|View full text |Cite|
|
Sign up to set email alerts
|

A Population-based Case–Control Study of Urinary Arsenic Species and Squamous Cell Carcinoma in New Hampshire, USA

Abstract: Background: Chronic high arsenic exposure is associated with squamous cell carcinoma (SCC) of the skin, and inorganic arsenic (iAs) metabolites may play an important role in this association. However, little is known about the carcinogenicity of arsenic at levels commonly observed in the United States.Objective: We estimated associations between total urinary arsenic and arsenic species and SCC in a U.S. population.Methods: We conducted a population-based case–control SCC study (470 cases, 447 controls) in a U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 56 publications
(65 reference statements)
0
117
1
Order By: Relevance
“…Long-term exposure to arsenite has been reported to induce numerous human health effects, including lung cancer and several other types of cancers (IARC, 2012;Surdu et al, 2013;Gilbert-Diamond et al, 2013). Although the evidence of the carcinogenicity of inorganic arsenic in humans is strong, the exact molecular mechanisms of inorganic arsenic carcinogenesis remain poorly understood (IARC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to arsenite has been reported to induce numerous human health effects, including lung cancer and several other types of cancers (IARC, 2012;Surdu et al, 2013;Gilbert-Diamond et al, 2013). Although the evidence of the carcinogenicity of inorganic arsenic in humans is strong, the exact molecular mechanisms of inorganic arsenic carcinogenesis remain poorly understood (IARC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the differences between the arsenic concentrations in drinking water in Taiwan and America, as well as the potential regional differences, some scholars questioned the suitability of low-dose extrapolation of the Taiwanese data that the risk assessment models had relied on (Valberg et al 1998). In recent years, more and more studies have been published evaluating the association between arsenic in drinking water 2 L. Huang et al and health endpoints in low-to-moderate levels (Karagas et al 2002;Steinmaus et al 2003;Karagas et al 2004;Lamm et al 2004;Meliker et al 2010;García-Esquinas et al 2013;Gilbert-Diamond et al 2013). Across these research findings, SMRs from cancers were estimated as the ratio of the observed to the expected number of deaths based on the cause of death according to the gender of the reference population selected; some of them suggested a strong association between cancer and arsenic, as shown in Figure 2 (Chen et al 1985;Tsuda et al 1995;Buchet & Lison 1998;Hopenhayn-Rich et al 1998;Smith et al 1998;Lewis et al 1999;Tsai et al 1999;Nakadaira et al 2002;Chung, Huang, et al 2013).…”
Section: Arsenic Exposure Worldwidementioning
confidence: 99%
“…There are concerns over whether this limit is appropriate for populations in the United States since this standard was based on low-dose extrapolation of the Taiwanese data as discussed above. In this case, several studies have been conducted in the United States to explore the association between low-level arsenic exposure and cancers of the bladder (Bates et al 1995;Karagas et al 2002;Steinmaus et al 2003;Karagas et al 2004;Lamm et al 2004;Meliker et al 2010;García-Esquinas et al 2013), lung (Heck et al 2009;Putila & Guo 2011;Dauphiné et al 2013;García-Esquinas et al 2013), and skin (Karagas et al 2001(Karagas et al , 2002Knobeloch et al 2006;Gilbert-Diamond et al 2013). However, studies have encountered two stumbling blocks for the risk assessment of low-to-moderate arsenic exposure: inadequate sample sizes and exposure misclassification, which may bias results toward the null (Karagas et al 2004).…”
Section: United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic arsenic (arsenate and/or arsenite) has long been recognized as human carcinogens by the International Agency for Research on Cancer (IARC) [3]. Long-term exposure to inorganic arsenic can cause numerous human health effects, including several types of cancers [3][4][5], cardiovascular disease, and diabetes [6,7]. In addition, arsenicosis is a serious and widespread global public health problem [8] with more than 200 million people at risk of toxic arsenic exposure from ground water and food contamination [9].…”
Section: Introductionmentioning
confidence: 99%